Molecular markers in studies on fish parasites (Platyhelminthes): Review - Graça, Rodrigo Junio da; Fabrin, Thomaz Mansini Carrenho; Gasques, Luciano Seraphim; Prioli, Sônia Maria Alves Pinto; Prioli, Alberto José; Takemoto, Ricardo Massato (Acta Scientiarum. Biological Sciences, 2016)
Studies with molecular markers are currently more common for all groups of living organisms. Molecular techniques used in Platyhelminthes parasites of fishes do not merely reveal complex life cycles, but are important for species distinction and the elucidation of the phylogenetic hypothesis. Current research verified which molecular markers were mainly used phylogenetic studies on Platyhelminthes parasites of fish so that subsidies for further phylogenetic studies in Icthyoparasitology could be provided. Data base of CAPES Journals platform was employed for bibliometric analysis comprising the keywords “fish” and “phylogeny” associated with “Cestoda”, “Digenea” or “Monogenea”. Information retrieved was quantified and tabulated. Most studies were on Monogenea (43%), followed by Digenea (37%) and Cestoda (18%). Ribosomal molecular markers were the most used in the phylogenetic studies for fish parasites. Due to the advance of molecular biology techniques and of bioinformatics, with more robust phylogenetic analysis, the use of these techniques in other areas such as Ichytioparasitology is on the increase. In fact, molecular phylogenetics and morphological structures analysis have efficiently contributed towards the understanding of phylogenetic relationships among the groups.